2018
DOI: 10.1186/s13148-018-0522-z
|View full text |Cite
|
Sign up to set email alerts
|

Paternal sepsis induces alterations of the sperm methylome and dampens offspring immune responses—an animal study

Abstract: BackgroundSepsis represents the utmost severe consequence of infection, involving a dysregulated and self-damaging immune response of the host. While different environmental exposures like chronic stress or malnutrition have been well described to reprogram the germline and subsequently offspring attributes, the intergenerational impact of sepsis as a tremendous immunological stressor has not been examined yet.MethodsPolymicrobial sepsis in 12-week-old male C57BL/6 mice was induced by cecal ligation and punctu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…Further, recurrent methylation of this promoter may contribute to “endotoxin tolerance” in the sepsis-associated immune suppression observed in later stages of the disease ( 96 ). Male (but not female) offspring of fathers subjected to CLP were shown to have a depressed response 24 hours after a subsequent endotoxin challenge, with lower plasma concentrations of IL-6, TNF-α, and IL-10 ( 97 ). Interestingly, these findings were attributed to alterations in sperm DNA methylation, providing evidence for intergenerational sex-dependent differences mediated via epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recurrent methylation of this promoter may contribute to “endotoxin tolerance” in the sepsis-associated immune suppression observed in later stages of the disease ( 96 ). Male (but not female) offspring of fathers subjected to CLP were shown to have a depressed response 24 hours after a subsequent endotoxin challenge, with lower plasma concentrations of IL-6, TNF-α, and IL-10 ( 97 ). Interestingly, these findings were attributed to alterations in sperm DNA methylation, providing evidence for intergenerational sex-dependent differences mediated via epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that epigenetic changes can endure [49], with even transgenerational effects such as alterations in DNA-methylation found in a murine model of sepsis survivors [50]. Although DNA-methylation especially at CpG sites of the genome represents another known determinant of CTCF occupancy [51], it is so far unknown whether CTCF binding itself is a PLOS ONE long-lasting or even heritable epigenetic mark in human disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also examined the metabolic changes associated with polymicrobial sepsis using a cecal ligation and puncture model ( 9 ). These studies have observed similar outcomes as LPS administration including fever, weight loss, decrease activity, and decreased food and water consumption ( 9 12 ).…”
Section: Introductionmentioning
confidence: 79%